Natural hybridization between two butterfly bushes in Tibet: dominance of F(1) hybrids promotes strong reproductive isolation - Liao, Rongli (BMC Plant Biol, 2021)
BACKGROUND: It has been recognized that a certain amount of habitat disturbance is a facilitating factor for the occurrence of natural hybridization, yet to date we are unaware of any studies exploring hybridization and reproductive barriers in those plants preferentially occupying disturbed habitats. Buddleja plants (also called butterfly bush) generally do grow in disturbed habitats, and several species with hybrid origin have been proposed, based solely on morphological evidence. RESULTS: In the present study, we test the hypothesis that B. × wardii is of natural hybridization origin in two sympatric populations of three taxa including B. × wardii and its parents (B. alternifolia and B. crispa) plus 4 referenced parental populations, using four nuclear genes and three chloroplast intergenic spacers, as well as with 10 morphological characters. Our results suggest that at both sites B. × wardii is likely to be a hybrid between B. alternifolia and B. crispa, and moreover, we confirm that most of the hybrids examined are F(1)s. That these plants are F(1)s is further supported by morphology, as no transgressive characters were detected. B. crispa was found to be the maternal parent in the Bahe (BH) population, from cpDNA evidence. However, in the Taji (TJ) population, the direction of hybridization was difficult to establish due to the shared cpDNA haplotypes between B. alternifolia and B. crispa, however we still predicted a similar unidirectional hybridization pattern due to results from cross-specific pollination treatments which supported the “SI × SC rule”. CONCLUSIONS: The presence of mainly F(1) hybrids can successfully impede gene flow and thus maintain species boundaries in parental species in a typical distribution of Buddleja, i.e. in disturbed habitats. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12870-021-02909-7.